Harmonious Society and Chinese CSR: Is There Really a Link? - See, Geoffrey (Kok Heng) (Journal of business ethics, 2009)
In 2005, Chinese President Hu Jintao instituted a “Harmonious Society” policy marking a new China’s approach toward development. This generated intense excitement among observers of Corporate Social Responsibility (CSR) who perceive an overlap in objectives between CSR and Harmonious Society and believe that Harmonious Society will lead to increased CSR engagement in China. However, there is little exploration of how Harmonious Society will contribute to increasing CSR engagement. This article seeks to explore whether Harmonious Society will meet this promise. It does so by drawing up a list of actions that if taken by the government would increase the level of CSR in China and make Harmonious Society a relevant factor in the development of Chinese CSR. To do so, my article studies comparative literature on CSR development to develop a framework that divides causes of CSR in a country into environmental constraints and discretionary responses. Understanding what drives the development of CSR allows us to understand what measures the Chinese government can take to influence the level of CSR. Using this framework, my article suggests that Harmonious Society is unlikely to promote CSR in China’s growing private sector because policy measures that affect the “constraints” driving CSR are bounded by other political considerations.